Three-dimensional models applied to offshore oil rigs engineering: Drilling steps and environmental risks - Zampirolli, Brian Siqueira (2020)
Oil is the main source of energy in the current world capable of supplying an immense market, moving a large part of the world economy. It is a complex compound, extracted by drilling exploration wells on land or at sea. At sea, the extraction process is more complex and also has a higher risk inherent to the environment. The joint work associated with the development of new technologies and public policies, allows the activity to be less impactful every day. The present work integrates previous models and provides new three-dimensional models, in order to allow the detailing of the oil extraction processes, associating the environmental risks to the exploration, profiling, completion and production stages and the mechanisms of control and remediation of impacts.